Estimation of Regional Wage Series in Chile - Dresdner, Jorge (Estudios de Economía, 2016)
Monthly wage series with quarterly periodicity between December 1994 andDecember 2004 for thirteen regions in Chile are presented in this paper. Theseseries are based on the information recollected by the Superintendencia de Fondosde Pensiones (Pensions Fund Superintendence), but are corrected for truncationand censoring bias. The comparative analysis of corrected and non-correctedseries indicates that the series show a statistically diferentiated behavior. Thenon-corrected wage series are not good predictors of the corrected series.Thus, to develop regional wage analysis, based on this information source, it ispreferable to use the corrected series presented in this paper.